The Effect of Facilities and Service Quality on Passenger Loyalty Through Passenger Satisfaction Using MRT (MASS Rapid Transit) Transportation Services - Evi Herawati; Euis Saribanon; Cecep Pahrudin; Juliater Simarmata; Reni Dian Octaviani (Dinasti Review, 2026)
Public transportation plays a vital role in urban mobility, especially in major cities like Jakarta. One of the modes of transportation expected to reduce congestion is the Mass Rapid Transit (MRT). Since its operation, MRT Jakarta has become a preferred alternative due to its speed and punctuality. This study aims to analyze the influence of facilities and service quality on usage loyalty through passenger satisfaction as a mediating variable. By understanding the relationship among these variables, this research seeks to provide strategic recommendations for MRT Jakarta management to improve service quality and retain user loyalty. The research method used is descriptive with a quantitative approach. The population of this study comprises all MRT users in Jakarta, totaling 33,496,540 (MRT, 2024). Based on Slovin's formula, a sample of 400 respondents was determined. Data were collected using both secondary data (journals, previous research, MRT data) and primary data through questionnaires. The analysis method employed is Structural Equation Modeling (SEM), a statistical technique used to build and test causal relationship models. The results indicate that both facilities and service quality have significant direct and indirect effects on usage loyalty, with passenger satisfaction serving as a crucial mediating factor.